Investigation of Workers' Food and Suggestions as to Dietary - Hill, Leonard, Sir, 1866- (London : His Majesty's Stationery Office)
1917-10 1917 1910s 12 pages 7 TABLE II. Source of Meal. Ingredients. Gross. Weight in Grammes. Calories. Dry. Protein. Fat. Carbohydrate. Women's restaurant Roast mutton 50 29.0 13.0 109.0 687 Boiled potatoes 123 Cabbage 73 Syrup roll 157 Women's tea shop Roll 50 8.4 8.0 70.0 397 Butter 8 Milk 15 Sugar 10 Stewed prunes 67 Syrup 20 Girl's canteen — Meat dishes Stewed steak 92 39.0 4.0 56.0 426 Potatoes 200 Peas 70 Roast beef 69 26.5 3.1 34.9 281 Potatoes 127 Cabbage 47 Roast mutton 66 25.7 3.0 36.1 281 Potatoes 117 Cabbage 98 Extra and Sweet dishes Stewed fruit and custard 276 5.8 3.3 60.0 300 Rice pudding 133 3.1 2.4 32.0 166 Seed cake and bun loaf 72 3.9 6.0 46.3 262 Roll 61 5.3 7.1 34.0 227 Butter 9 Meals brought from home Meat 87 29.5 34.9 93.7 830 Potato 100 Pastry 36 Rabbit 112 51.5 54.2 104.4 1,143 Pastry 215 Roast pork 70 32.8 14.4 77.2 590 Yorkshire pudding 72 Potatoes 128 Cabbage 94 Roast beef 78 30.4 4.7 30.8 295 Potatoes 64 Cabbage 71 Haricot beans 50 12. Hostel Dietaries.— The erection of hostels, required on account of the inadequacy of pre-existing accommodation for housing the suddenly increased personnel of certain large munition factories, has afforded an opportunity of investigating the whole daily dietary of operatives. The investigation was made at a well-managed hostel where each worker may eat as much as he or she desires. In the dining hall there are separate tables for men and women ; and by weighing the food supplied to a definite number at given tables, and by weighing the uneaten residue, the cost of each ingredient being known, the management obtained the cost price of food per week, and found it amounted, in March, 1916, to 15s. 2d. per man, and 11s. 9¾d. per woman. This gives a consumption for a woman of 0.8 that for a man, a ratio in agreement with that stated above. The amounts of protein, fat, and carbohydrate present in the food consumed were estimated by two schemes :— (a) The management weighed the amount of each type of food supplied throughout the day to (a) six men and (b) six women, and deducted the amounts unconsumed. The amounts of protein, fat and carbohydrate present were determined at the laboratory from known data. (b) The hostel was visited personally and the amounts of all the most important constituents of the menu actually eaten by a large number of persons were weighed ; the average daily ration consumed per person was calculated from these data, and then samples of the foodstuffs were analysed as above. 127/NU/5/5/1/1